Challenges in Cost-effective Automated Detection of Enameled Flat Wires in the Context of Robot-based Stator Manipulation - Vogel, Alexander; Morello, Andreas; Mahr, Alexander; Franke, Jörg; Kühl, Alexander (2022 12th International Electric Drives Production Conference (EDPC), 2022)
Especially in the production of electric drives, highly efficient drives in new use cases are needed to reach global climate targets. To obtain maximum motor power with minimal motor weight, it is necessary to fill the stator slots with a maximum of copper. In the past, the round wire has been the state of the art. However, with increasing efficiency expectations, round wires cannot reach the performance targets anymore. Form coils, also known as hairpins, are one common technology with higher fill factors. In addition, winding processes with endless flat or rectangle wires are currently in development and could fulfill the demand for electric drives in the future. Accompanied by new joining solutions, this technology could lower the production cost on the one hand and reduce the contacting spots with potentially increased contacting resistance on the other hand. One challenge in the automation of their winding and joining is a fully automated process chain, starting with the winding process and ending with end-of-line testing. One thing, all process steps have in common is the requirement to detect the position of the wires with high precision. This detection is fundamental to subsequent steps, performed by smart robot-based machines.<br
Keywords: wire detection; flat wire; image recognition; stator manipulation; stator manufacturing automation; electric drives production